Analogue black holes and scalar-dilaton theory - Moss, Ian G. (Comptes Rendus. Physique)
This note analyses the long wavelength dynamics of a two horizon analogue black hole system in one spatial dimension. By introducing an effective scalar-dilaton model we show that closed form expressions can be obtained for the time-dependent Hawking flux and the energy density of the Hawking radiation. We show that, in the absence superluminal modes, there is a vacuum instability. This instability is recognisable to relativists as the analogue to the destabilisation of the Cauchy horizon of a black hole due to vacuum polarization.